Cell-Seeded Acellular Artery for Reconstruction of Long Urethral Defects in a Canine Model. (7th June 2021) - Zhong, Hao; Shen, Yamei; Zhao, Danhui; Yan, Guoqiang; Wu, Chengai; Huang, Guanglin; Liu, Zhizhong; Zhai, Jianpo; Han, Qin
Abstract : The management of urethral stricture remains a major therapeutic challenge in clinics. Herein, we explored the feasibility of reconstructing a relatively long segment of the urethra by the cell-seeded acellular artery in a canine model. The acellular arterial matrix was obtained from the excised carotid artery of donor dogs. Autologous adipose-derived stem cells (ADSCs) from 6 male dogs were grown and seeded onto the premade acellular arterial matrix. A 3 cm long segment of the urethra was resected in 12 male dogs. Urethroplasty was performed with the acellular arterial matrix seeded with ADSCs in 6 animals and without cells in 6. Serial urethrography was performed at 1 and 3 months postoperatively. Wide urethral calibers without any signs of strictures were confirmed in all 6 animals in the experimental group. In contrast, urethral stricture was demonstrated in 3 animals in the control group. The graft was highly epithelialized and smooth in the experimental group, while graft contracture and scar formation were showed in the control group. Histologic analysis of the cell-seeded arterial matrix at 1 month confirmed the presence of multilayered urothelium and muscle. The levels of tissue formation developed over time with a progressive increase in muscle content. In contrast, extensive fibrosis and sparse smooth muscle were seen in animals treated with matrix without ADSCs. This study provides preclinical evidence that the ADSC-seeded arterial matrix can be used as a tubularized scaffold in the reconstruction of 3 cm long urethral defect in a male canine model. The ADSC-seeded arterial matrix remodels and regenerates normal-appearing urethral tissue layers over time.